Lexems of Oriental origin in phraseologisms relating to humans in the language of Slavic Muslims in Bosnia - Vladimirovna Kuznetsova, Irina; Sergeevich, Khmelevskiy Mikhail (Slavia Centralis, 2021)
The authors discuss phraseological units of Bosnian Muslims with a semantically similar component such as an anthroponym of Oriental origin. The authors deal with both outdated phraseological units and those that are actively used nowadays. Due to the vastness of Oriental origin as a special genetic layer of South Slavic vocabulary, the authors analyse the expressions that denote a person in such aspects as intellect, title, position, occupation, etc., which are frequently used by Slavic Muslimsh, who live in Bosnia and Herzegovina and in the region of the Slavonic Balkans, in their everyday speech. The result of the five-century domination of the Ottoman Empire in the Balkan Peninsula is borrowing from theOld Ottoman (Old Turkish) language, which became both the source language and (often) the intermediate language through which Arabisms and Persisms entered the South Slavic recipient languages with part of Oriental culture and realities of everyday life.
Keywords: phraseology; South Slavic languages; Turkish language; Bosnia and Herzegovina; oriental lexical loanwords; standard language; dialects; anthroponym